3x-4y=12

Subtract 3x from both sides of the equation.

-4y=12-3x

Divide each term by -4 and simplify.

Divide each term in -4y=12-3x by -4.

-4y-4=12-4+-3x-4

Cancel the common factor of -4.

Cancel the common factor.

-4y-4=12-4+-3x-4

Divide y by 1.

y=12-4+-3x-4

y=12-4+-3x-4

Simplify each term.

Divide 12 by -4.

y=-3+-3x-4

Dividing two negative values results in a positive value.

y=-3+3×4

y=-3+3×4

y=-3+3×4

y=-3+3×4

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-3+3(0)4

Simplify -3+3(0)4.

Multiply 3 by 0.

y=-3+04

Divide 0 by 4.

y=-3+0

Add -3 and 0.

y=-3

y=-3

Use the x and y values to form the ordered pair.

(0,-3)

(0,-3)

Remove parentheses.

y=-3+3(1)4

Simplify -3+3(1)4.

Multiply 3 by 1.

y=-3+34

To write -3 as a fraction with a common denominator, multiply by 44.

y=-3⋅44+34

Combine -3 and 44.

y=-3⋅44+34

Combine the numerators over the common denominator.

y=-3⋅4+34

Simplify the numerator.

Multiply -3 by 4.

y=-12+34

Add -12 and 3.

y=-94

y=-94

Move the negative in front of the fraction.

y=-94

y=-94

Use the x and y values to form the ordered pair.

(1,-94)

(1,-94)

Remove parentheses.

y=-3+3(2)4

Simplify -3+3(2)4.

Multiply 3 by 2.

y=-3+64

Cancel the common factor of 6 and 4.

Factor 2 out of 6.

y=-3+2(3)4

Cancel the common factors.

Factor 2 out of 4.

y=-3+2⋅32⋅2

Cancel the common factor.

y=-3+2⋅32⋅2

Rewrite the expression.

y=-3+32

y=-3+32

y=-3+32

To write -3 as a fraction with a common denominator, multiply by 22.

y=-3⋅22+32

Combine -3 and 22.

y=-3⋅22+32

Combine the numerators over the common denominator.

y=-3⋅2+32

Simplify the numerator.

Multiply -3 by 2.

y=-6+32

Add -6 and 3.

y=-32

y=-32

Move the negative in front of the fraction.

y=-32

y=-32

Use the x and y values to form the ordered pair.

(2,-32)

(2,-32)

These are three possible solutions to the equation.

(0,-3),(1,-94),(2,-32)

Find Three Ordered Pair Solutions 3x-4y=12